2013
DOI: 10.1159/000353539
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Effectiveness of Humming on the Supraglottic Compression in Subjects with Muscle Tension Dysphonia

Abstract: Aims: To verify whether humming corrects supraglottic compression in muscle tension dysphonia (MTD) patients. Methods: We enrolled 23 MTD participants (13 male, 10 female) showing supraglottic compression. Each individual was instructed to perform 3 types of phonation under transnasal laryngofiberscopy: natural phonation, humming phonation without pitch change and subsequent um-hum phonation, i.e. humming with pitch glide up as if agreeing with someone. The degree of supraglottic compression was estimated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 28 publications
(40 reference statements)
1
19
1
4
Order By: Relevance
“…In our previous study, 11 to verify the former two description, we investigated the immediate effects of humming on the degree of supraglottic compression and verified that the combination of humming and subsequent um-hum phonation immediately relieves supraglottic compression by repositioning the false vocal folds, arytenoids, and petiole of the epiglottis in MTD patients as well as nondysphonic speakers. In the present study, to verify the latter two description, we investigated immediate effects of humming on the glottal condition, that is, EGG computed parameters for the degree of glottal contact as well as the irregularity of vocal fold vibration.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…In our previous study, 11 to verify the former two description, we investigated the immediate effects of humming on the degree of supraglottic compression and verified that the combination of humming and subsequent um-hum phonation immediately relieves supraglottic compression by repositioning the false vocal folds, arytenoids, and petiole of the epiglottis in MTD patients as well as nondysphonic speakers. In the present study, to verify the latter two description, we investigated immediate effects of humming on the glottal condition, that is, EGG computed parameters for the degree of glottal contact as well as the irregularity of vocal fold vibration.…”
Section: Discussionmentioning
confidence: 77%
“…Concerning the first hypothesis, our previous study 11 demonstrated that supraglottic compression is immediately released in humming-responsive MTD patients. The present series of MTD patients also exhibited supraglottic compression and produced successful humming and um-hum phonation.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Educational material with advice on voice care, educational videos on vocal anatomy and physiology, and incentive to attend lectures on voice health held by the hospital and teaching institution were used. The direct therapy was comprised of airflow control techniques [12, 17, 28], nasal sound exercises [17, 18, 29], laryngeal manual therapy [5, 20, 21], and semi-occluded vocal tract techniques with the use of Finnish resonance tubes and a high-resistance straw [24, 30]. …”
Section: Methodsmentioning
confidence: 99%